Negative electrode for lithium secondary battery and lithium secondary battery comprising the same

CN113809283BActive Publication Date: 2026-10-16SK ON CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110665684.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-16
Filing Date
2021-06-16
Publication Date
2026-10-16
Estimated Expiration
2041-06-16

AI Technical Summary

Technical Problem

然而,SiOx材料存在由于Si基材料与电解液之间的副反应导致的界面电阻增加和寿命特性劣化、由于体积膨胀导致的电极粘合力降低等问题,使得SiOx材料的应用受到限制

Benefits of technology

[0018] Various advantages and features of the present invention, as well as methods of implementing them, will become apparent from the following description of exemplary embodiments. However, the present invention is not limited to the exemplary embodiments described below, but can be implemented in various different forms. These exemplary embodiments are provided only to complete the invention and to enable those skilled in the art to fully appreciate the scope of protection of the invention, which is defined by the scope of the claims. Specific details of the implementation of the invention will be described in detail below, and "and/or" includes each and all combinations of one or more of the mentioned items.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003175522760000141
    Figure GDA0003175522760000141
  • Figure GDA0003175522760000151
    Figure GDA0003175522760000151
  • Figure GDA0003175522760000161
    Figure GDA0003175522760000161
Patent Text Reader

Abstract

Provided are a negative electrode for a lithium secondary battery, and a lithium secondary battery including the same. The negative electrode for a lithium secondary battery includes a current collector; a first negative electrode active material layer disposed on the current collector and including a first graphite-based active material including artificial graphite and natural graphite, and a first silicon-based active material; and a second negative electrode active material layer disposed on the first negative electrode active material layer and including a second graphite-based active material including artificial graphite and natural graphite, and a second silicon-based active material, wherein a content of the artificial graphite of the first graphite-based active material is equal to or less than a content of the natural graphite, and a content of the artificial graphite of the second graphite-based active material is greater than a content of the natural graphite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the negative electrode. Background Technology

[0002] Recently, with the emergence of global warming, the demand for environmentally friendly technologies as a countermeasure to global warming has increased rapidly. In particular, with the increasing demand for electric vehicles and energy storage systems (ESS) technologies, the demand for lithium-ion batteries as energy storage devices is surging. Therefore, research is underway to improve the energy density of lithium-ion batteries.

[0003] However, existing commercial lithium-ion batteries typically use graphite active materials such as natural and artificial graphite. The relatively low theoretical capacity of graphite (372 mAh / G) results in low energy density in these batteries. Therefore, research is underway to improve energy density by developing a novel anode material.

[0004] As a solution to improve energy density, a Si-based material with a high theoretical capacity (3580 mAh / g) has emerged. However, due to its large volume expansion (~400%) during repeated charging and discharging, this Si-based material suffers from deterioration in battery life characteristics. Therefore, to address the issue of large volume expansion in Si materials, SiO2, which has a lower volume expansion rate compared to Si, has been developed. x Materials. However, SiO x The material suffers from problems such as increased interfacial resistance and deteriorated lifetime characteristics due to side reactions between Si-based materials and electrolytes, and reduced electrode adhesion due to volume expansion, which makes SiO2... x The application of materials is limited. Summary of the Invention

[0005] One embodiment of the present invention aims to provide a high-capacity negative electrode, wherein negative electrode detachment is suppressed and quicklifespan characteristic is improved by improving the adhesion to the negative electrode current collector and by reducing the interfacial resistance by making the mixing ratio between natural graphite and artificial graphite in the negative electrode active material layer containing silicon-based material different from each other.

[0006] In one general aspect, a negative electrode for a lithium secondary battery includes: a current collector; a first negative electrode active material layer disposed on the current collector and including a first graphite-based active material containing artificial graphite and natural graphite and a first silicon-based active material; and a second negative electrode active material layer disposed on the first negative electrode active material layer and including a second graphite-based active material containing artificial graphite and natural graphite and a second silicon-based active material, wherein the content of artificial graphite in the first graphite-based active material is equal to or less than the content of natural graphite, and the content of artificial graphite in the second graphite-based active material is greater than the content of natural graphite.

[0007] The first graphite-based active material may contain artificial graphite and natural graphite in a weight ratio of 5:95 to 50:50.

[0008] The second graphite-based active material may comprise artificial graphite and natural graphite in a weight ratio of 97.5:2.5 to 55:45.

[0009] The first negative electrode active material layer may contain 0.1-35% by weight of a first silicon-based active material based on the total weight of the active material, and the second negative electrode active material layer may contain 0.1-35% by weight of a second silicon-based active material based on the total weight of the active material.

[0010] The first negative electrode active material layer may include 6-30% by weight of a first silicon-based active material based on the total weight of the active material, and the second negative electrode active material layer may include 6-30% by weight of a second silicon-based active material based on the total weight of the active material.

[0011] The negative electrode for a lithium secondary battery may also include a third negative electrode active material layer disposed on the second negative electrode active material layer and including a third graphite-based active material containing artificial graphite.

[0012] The third graphite-based active material can be granular-type or bimodal-type artificial graphite, and can have a particle size of 13-20 μm.

[0013] The third negative electrode active material layer can have a density of 1.55-1.8 g / cm³. 3 The density.

[0014] The thickness ratio between the first negative electrode active material layer and the second negative electrode active material layer can be greater than 3:7 and less than 7:3.

[0015] Based on the total thickness of the negative electrode active material layer, the thickness of the third negative electrode active material layer can be 0.5%-15%.

[0016] The first negative electrode active material layer and the second negative electrode active material layer can have a continuous active material concentration gradient at their interface.

[0017] On the other hand, a lithium secondary battery is provided, comprising a negative electrode, a positive electrode, a separator, and an electrolyte as described above. Detailed Implementation

[0018] Various advantages and features of the present invention, as well as methods of implementing them, will become apparent from the following description of exemplary embodiments. However, the present invention is not limited to the exemplary embodiments described below, but can be implemented in various different forms. These exemplary embodiments are provided only to complete the invention and to enable those skilled in the art to fully appreciate the scope of protection of the invention, which is defined by the scope of the claims. Specific details of the implementation of the invention will be described in detail below, and "and / or" includes each and all combinations of one or more of the mentioned items.

[0019] Unless otherwise defined, all terms used herein (including technical and scientific terms) may have the meanings commonly understood by those skilled in the art. Throughout this specification, unless expressly stated to the contrary, the word "comprising" of any element shall be understood to imply the further inclusion of other elements rather than the exclusion of any other elements. Furthermore, unless expressly stated to the contrary, the singular form herein includes the plural form.

[0020] It should be understood that when an element such as a layer, membrane, region, or plate is referred to as being "on" or "above" another element, it may be "directly" on the other element or there may be an intermediate element between them.

[0021] In an exemplary embodiment of the present invention, a negative electrode for a lithium secondary battery is provided. The negative electrode includes a current collector; a first negative electrode active material layer disposed on the current collector and including a first graphite-based active material containing artificial graphite and natural graphite and a first silicon-based active material; and a second negative electrode active material layer disposed on the first negative electrode active material layer and including a second graphite-based active material containing artificial graphite and natural graphite and a second silicon-based active material, wherein the content of artificial graphite in the first graphite-based active material is equal to or less than the content of natural graphite, and the content of artificial graphite in the second graphite-based active material is greater than the content of natural graphite.

[0022] Examples of current collectors may be, but are not limited to, selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with conductive metal, and combinations thereof.

[0023] The first negative electrode active material layer is disposed on the current collector and includes a first graphite-based active material containing artificial graphite and natural graphite, and a first silicon-based active material.

[0024] The first graphite-based active material is characterized by having an artificial graphite content equal to or less than that of natural graphite. The first negative electrode active material layer can improve the adhesion between the silicon-based material and the negative electrode current collector by increasing the proportion of natural graphite-based material and relatively decreasing the proportion of artificial graphite-based material in the first graphite-based material. Specifically, during the lithium-ion insertion / extraction process, the stress caused by the volume expansion of the silicon-based active material is alleviated, thereby suppressing the expansion of the negative electrode active material and increasing its adhesion. This can suppress electrode detachment, thus further improving the interfacial resistance and adhesion between the current collector and the negative electrode active material layer.

[0025] Based on the total weight of the first graphite-based active material and the second graphite-based active material, the negative electrode may include artificial graphite and natural graphite in a weight ratio of 6:4 to 8:2, preferably 6.5:3.5 to 7.5:2.5.

[0026] Typically, attempts are made to improve capacity characteristics by using silicon-based active materials as anode materials. However, volume expansion of the active material and irreversible side reactions in the electrolyte result in the mixing of silicon-based active materials with a large amount of graphite-based active materials. Natural graphite, as a graphite-based active material, performs poorly due to increased resistance caused by high-rate charging and discharging, while artificial graphite does not suppress the expansion characteristics of silicon-based active materials, thus exhibiting poor lifetime characteristics. In this invention, to address the above problems, a specific weight ratio of artificial to natural graphite within a certain range is used to improve high-rate charging / discharging characteristics. Furthermore, different graphite mixtures are used for the first and second anode active material layers to improve high-rate charging capacity by reducing resistance. Therefore, excellent charging, output, lifetime, and fast lifetime characteristics can be ensured.

[0027] The first graphite-based active material may comprise artificial graphite and natural graphite in a weight ratio of 5:95 to 50:50, preferably in a weight ratio of 10:90 to 45:55, and more preferably in a weight ratio of 25:75 to 40:60. When the graphite-based active material is composed of the aforementioned content ratio, the first negative active material layer can further improve the adhesion between the silicon-based material and the negative current collector. Meanwhile, when the weight ratio of artificial graphite to natural graphite is less than 5:95, the content of artificial graphite in the first negative active material layer in contact with the current collector is too low, resulting in poor output characteristics and lifespan maintenance rate. Conversely, when the weight ratio of artificial graphite to natural graphite exceeds 50:50, the proportion of natural graphite is insufficient, leading to insufficient adhesion to the negative current collector caused by the volume expansion of the silicon-based active material.

[0028] In addition, the first graphite-based active material may be a combination of natural graphite and artificial graphite, may have a particle size of 8-20 μm, and may have, but is not limited to, an amorphous shape, a plate shape, a flake shape, a spherical shape or a fibrous shape.

[0029] The first silicon-based active material may be a silicon-based substance, such as Si, SiO x (0<x<2), a Si-Q alloy (wherein Q is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), a silicon-carbon composite, or a mixture of at least one of the foregoing with SiO₂. The first silicon-based active material is preferably Si or SiO x (0<x<2), more preferably SiO x (0<x<2).

[0030] The first silicon-based active material particles may have an average particle size of less than 30 μm and greater than 2 μm, preferably less than 20 μm and greater than 5 μm, and more preferably less than 10 μm and greater than 7 μm. Within the above range, the volume expansion of the negative active material particles during lithium ion intercalation / deintercalation is reduced, so that electrode deterioration can be suppressed.

[0031] Furthermore, based on the total weight of the active material contained in the first negative electrode active material layer, the content of the first silicon-based active material can be 0.1-35% by weight, 1-30% by weight, or 3-30% by weight. Based on the total weight of the active material contained in the first negative electrode active material layer, the content of the first silicon-based active material can more specifically be 6-30% by weight, preferably 6-20% by weight, and more preferably 9-20% by weight. The above-mentioned content range of the silicon-based active material can prevent a rapid increase in the ratio of the increase in volume expansion rate to the increase in battery energy density; therefore, fast-charging life can be maintained at a very high level.

[0032] In the negative electrode according to an exemplary embodiment of the present invention, a second negative electrode active material layer is disposed on a first negative electrode active material layer, and includes a second graphite-based active material and a second silicon-based active material containing artificial graphite and natural graphite.

[0033] The second graphite-based active material is characterized by a higher content of artificial graphite than natural graphite. That is, the fast-charging characteristics and lifespan retention of the second anode active material layer, which includes silicon-based materials, can be improved by increasing the proportion of artificial graphite-based material and minimizing the proportion of natural graphite-based material in the second graphite-based active material.

[0034] The second graphite-based active material can contain artificial graphite and natural graphite in a weight ratio of 97.5:2.5 to 55:45, preferably 95:5 to 55:45, and more preferably 90:10 to 60:40. When the graphite-based active material is composed of the aforementioned content ratio, the second negative electrode active material layer can further improve high-rate charging characteristics. On the other hand, when the weight ratio of artificial graphite to natural graphite is less than 55:45, the content of artificial graphite in the second negative electrode active material layer decreases, resulting in insufficient achievement of fast charging characteristics and lifespan retention. Conversely, when the weight ratio of artificial graphite to natural graphite exceeds 97.5:2.5, the proportion of natural graphite is insufficient, leading to a decrease in the interfacial adhesion between the first and second negative electrode active material layers, which in turn may cause a rapid increase in the negative electrode interfacial resistance due to the volume expansion of the second silicon-based active material.

[0035] The second graphite-based active material may have the same physical properties as the first graphite-based active material as described by its shape and average particle size, and active materials that are the same as or different from the first graphite-based active material may be used as the second graphite-based active material.

[0036] The second silicon-based active material can be the same material as those described as the type of the first silicon-based active material, and active materials that are the same as or different from the first silicon-based active material can be used as the second silicon-based active material.

[0037] Furthermore, based on the total weight of the active material contained in the second negative electrode active material layer, the content of the second silicon-based active material can be 0.1-35% by weight, 1-30% by weight, or 3-30% by weight. Based on the total weight of the active material contained in the second negative electrode active material layer, the content of the second silicon-based active material can more specifically be 6-30% by weight, preferably 6-20% by weight, and more preferably 9-20% by weight. The above-mentioned content range of the silicon-based active material can prevent a rapid increase in the ratio of the increase in volume expansion rate to the increase in battery energy density; therefore, fast-charging life can be maintained at a very high level.

[0038] The negative electrode for a lithium secondary battery according to an exemplary embodiment of the present invention may further include a third negative electrode active material layer, which is disposed on a second negative electrode active material layer and includes a third graphite-based active material containing artificial graphite. Meanwhile, the upper layer of the electrode (the third negative electrode active material layer) is the region in contact with excess electrolyte, making the electrolyte prone to side reactions. When the electrolyte is in direct contact with the silicon-based active material, the electrode will significantly shrink / expand during the lithium-ion insertion / extraction process, thereby creating a new interface. This can easily lead to irreversible electrolyte consumption due to side reactions. As a result, a cell deterioration mode occurs, causing a rapid decrease in battery life retention.

[0039] In this invention, the active material of the third negative electrode active material layer consists only of graphite-based active material, and the expansion / contraction of the active material is less than that of the silicon-based active material. This improves the isolation phenomenon of the active material caused by charging and discharging. Therefore, when the battery is repeatedly charged and discharged, excessive contact between the electrolyte and the silicon-based active material can be prevented to minimize side reactions and suppress the expansion of the electrode in the thickness direction of the silicon-based active material. This also prevents excessive increase in resistance during rapid life evaluation.

[0040] The third graphite-based active material can be surface-coated granular or bimodal artificial graphite with a particle size of 13-20 μm, and preferably can be surface-coated granular artificial graphite with a particle size of 16-20 μm.

[0041] The third graphite-based active material, namely surface-coated granular or bimodal artificial graphite, is an active material with excellent output, fast charging and lifespan maintenance. Therefore, the output (e.g., 10-second resistance and output) and fast charging (with improved lithium intercalation in the upper layer of the electrode) that indicate short-term battery characteristics can be improved through the third negative electrode active material.

[0042] The surface coating of the third graphite-based active material can specifically include at least a portion of the surface of the graphite particles. The carbon coating is formed of hard carbon, soft carbon, heavy oil, or pitch, and can be an amorphous carbon coating. As a non-limiting example, hard carbon can be heat-treated at a temperature of 700-1200°C for 3-6 hours to produce a coating, and soft carbon can be heat-treated at a temperature of 1000-1300°C for 3-6 hours to produce a coating, but the invention is not limited thereto.

[0043] Meanwhile, particle size can refer to D50, which is the particle diameter at which 50% of the cumulative volume is accumulated, starting from the smallest particle diameter, when the particle size distribution is measured using laser scattering. Here, D50 can be obtained by collecting samples of carbonaceous material prepared according to KS AISO 13320-1 standard and measuring the particle size distribution using a Mastersizer 3000 (Malvern). Specifically, ethanol can be used as a solvent, and if necessary, dispersion can be performed using an ultrasonic disperser, after which the bulk density can be measured.

[0044] In the negative electrode according to an exemplary embodiment of the present invention, the density of the third negative electrode active material layer can be 1.55-1.8 g / cm³. 3 The preferred value is 1.6-1.8 g / cm³. 3 More preferably, it is 1.65-1.8 g / cm³. 3 .

[0045] The first negative electrode active material layer, the second negative electrode active material layer, and the third negative electrode active material layer may include an adhesive and may optionally further include a conductive material.

[0046] Adhesives are used to bond negative electrode active material particles well together and also to bond negative electrode active material well to current collectors. Examples of water-based adhesives include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof. Specifically, adhesives can be composed of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and mixtures thereof.

[0047] Conductive materials are used to impart conductivity to electrodes, provided they do not cause chemical changes in the battery to be constructed and are electronically conductive. Examples of conductive materials include carbon-based materials such as graphite, carbon black, acetylene black, Ketjen black, carbon fibers, etc.; metal-based materials such as metal powders (e.g., copper, nickel, aluminum, and silver) or metal fibers; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0048] Meanwhile, based on the total weight of the first negative electrode active material layer, the second negative electrode active material layer and the third negative electrode active material layer, the content of the adhesive and the conductive material can be 1-10% by weight, preferably 1-5% by weight, more preferably 1-3% by weight, but the present invention is not limited thereto.

[0049] In the negative electrode according to an exemplary embodiment of the present invention, the thickness ratio between the first negative electrode active material layer and the second negative electrode active material layer can be greater than 3:7 and less than 7:3, preferably 4:6 to 6:4, and more preferably 4.5:5.5 to 5.5:4.5.

[0050] If the thickness ratio between the first and second negative electrode active material layers is greater than 3:7, the adhesion between the current collector (Cu substrate surface) and the first negative electrode active material layer is sufficient. This can suppress electrode detachment caused by the volume expansion of the first silicon-based active material in the first negative electrode active material layer, and improve the reduction in battery capacity and the sharp decline in battery life caused by increased resistance. Furthermore, electrode output characteristics and lifespan can be improved by suppressing the decrease in porosity of the first negative electrode active material layer during electrode rolling. For example, as the thickness of the second negative electrode active material layer, which contains a large amount of artificial graphite with hard particle strength, increases, a greater load is applied to the first negative electrode active material layer, which contains a large amount of natural graphite with relatively weak particle strength, during electrode rolling. This may lead to problems such as decreased porosity due to changes in appearance caused by particle pressing.

[0051] If the thickness ratio between the first and second negative electrode active material layers is less than 7:3, the proportion of natural graphite with a high expansion rate during electrode charging / discharging decreases, thus avoiding problems such as increased resistance and reduced lifetime retention caused by increased electrode thickness. Furthermore, as the thickness of the second negative electrode active material layer increases, the content of artificial graphite, which has excellent output, high-rate charging, and lifetime characteristics, increases, thereby improving the fast-charging lifetime retention rate.

[0052] Based on the total thickness of the first, second, and third negative electrode active material layers, the thickness of the third negative electrode active material layer can be 0.5%-15%. If the thickness of the third negative electrode active material layer is greater than 0.5% of the total thickness, electrode deformation caused by the volume expansion of the second silicon-based active material in the second negative electrode active material layer during charging / discharging can be suppressed. Therefore, the possibility of the third negative electrode active material undergoing isolation due to charging / discharging is reduced, thereby preventing side reactions between the second silicon-based active material and the electrolyte. If the thickness of the third negative electrode active material layer is less than 15% of the total thickness, it is preferred because the content of the third graphite-based active material is low, and the total content of the first and second silicon-based active materials, which greatly contribute to the cell capacity expression, is relatively increased, resulting in sufficient capacity of a high-capacity negative electrode achieved through silicon-based active materials.

[0053] Simultaneously, the first and second negative electrode active material layers possess a continuous concentration gradient of active materials at their interface. Specifically, the continuous concentration gradient of active materials refers to the continuous concentration gradient between the first silicon-based active material and the second silicon-based active material, and between the first graphite-based active material and the second graphite-based active material. Furthermore, even at the interface between the second and third negative electrode active material layers, the second silicon-based active material, the second graphite-based active material, and the third graphite-based active material can possess a continuous concentration gradient.

[0054] The concentration gradient at the interface between the first negative electrode active material layer and the second negative electrode active material layer, or at the interface between the second negative electrode active material layer and the third negative electrode active material layer, can be formed by simultaneously coating the first negative electrode slurry and the second negative electrode slurry or the second negative electrode slurry and the third negative electrode slurry during the manufacturing process of the negative electrode, and this coating method can be used with conventionally known methods.

[0055] In another exemplary embodiment, a lithium secondary battery is provided, which includes a negative electrode; a positive electrode; a separator; and an electrolyte.

[0056] The negative electrode is the same as described above.

[0057] The positive electrode includes a current collector and a layer of positive electrode active material formed by applying a positive electrode slurry containing positive electrode active material onto the current collector.

[0058] The negative electrode current collector described above can be used as the current collector, and any material known in the art can be used, but the present invention is not limited thereto.

[0059] The positive electrode active material layer may include the positive electrode active material and, optionally, may further include a binder and a conductive material. The positive electrode active material may be any positive electrode active material known in the art. As an example of a positive electrode material, a composite oxide of lithium with a metal selected from cobalt, manganese, nickel, and combinations thereof is preferred, but the invention is not limited thereto.

[0060] The above-described negative electrode adhesive and negative electrode conductive material can be used as the adhesive and conductive material, and any material known in the art can be used, but the present invention is not limited thereto.

[0061] The separator can be selected from, for example, glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene, or combinations thereof, and can be in the form of nonwoven or woven fabric. For example, in lithium secondary batteries, separators made primarily of polyolefin-based polymers (e.g., polyethylene and polypropylene) can be used, and separators coated with compositions containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength. Furthermore, the separator can optionally be used in a single-layer or multi-layer structure, and any separator known in the art can be used, but the invention is not limited thereto.

[0062] The electrolyte consists of organic solvents and lithium salts.

[0063] Organic solvents serve as a medium through which ions participating in the electrochemical reactions of the battery can move, and examples of organic solvents include carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvents. Organic solvents can be used alone or in combination of two or more, and the mixing ratio when using more than one combination can be appropriately adjusted according to the desired battery performance. Furthermore, any organic solvent known in the art can be used, but the invention is not limited thereto.

[0064] Lithium salts are substances dissolved in organic solvents that serve as the source of lithium ions in batteries, enabling the basic operation of lithium-ion secondary batteries and facilitating the movement of lithium ions between the positive and negative electrodes. Examples of lithium salts include, but are not limited to, LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO3C2F5)2, LiN(CF3SO2)2, LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, and LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are natural numbers), LiCl, LiI, LiB(C2O4)2 or combinations thereof.

[0065] The concentration of lithium salts that can be used is in the range of 0.1M to 2.0M. If the concentration of lithium salts is within this range, the electrolyte has appropriate conductivity and viscosity, thereby achieving excellent electrolyte performance and efficient lithium ion movement.

[0066] Furthermore, to improve charging / discharging characteristics, flame retardant properties, etc., the electrolyte may, if desired, further contain pyridine, triethyl phosphate, triethanolamine, cyclic ethers, ethylenediamine, n-glycine dimethyl ether (n-glyme), triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, the electrolyte may also further include halogen-containing solvents (e.g., carbon tetrachloride and ethylene trifluoride) to impart non-flammability, and may further contain fluoroethylene carbonate (FEC), propylene sulfone (PRS), fluoropropylene carbonate (FPC), etc., to improve high-temperature storage characteristics.

[0067] The lithium secondary battery according to the present invention, used to achieve the above-mentioned objectives, can be prepared by: sequentially stacking a manufactured negative electrode, a separator, and a positive electrode to form an electrode assembly; placing the resulting electrode assembly into a cylindrical battery case or a prismatic battery case; and then injecting an electrolyte. Alternatively, the electrode assembly can be stacked and then immersed in an electrolyte, and the resulting product can be placed in a battery case and sealed to manufacture a lithium secondary battery.

[0068] The battery casing used in this invention can be a battery casing commonly used in the battery field. The appearance of the battery casing is not limited by the purpose of the battery and can be, for example, cylindrical, angular, pouch-shaped or coin-shaped like a can.

[0069] The lithium secondary battery according to the present invention can be preferably used not only as a battery cell for powering small devices, but also as a single cell in medium or large battery modules comprising multiple battery cells. Preferred examples of medium or large devices include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.

[0070] Preferred embodiments and comparative examples of the present invention will be described below. However, the following embodiments are merely preferred embodiments of the present invention, and the present invention is not limited to these embodiments.

[0071] Example

[0072] (Example 1)

[0073] <Manufacturing the Negative Electrode>

[0074] 90.4 wt% of a first graphite-based active material (in which artificial graphite (D50: 20 μm) and natural graphite (D50: 10 μm) are mixed at a weight ratio of 5:5), 6.0 wt% of silicon oxide (SiO x , 0<x<2, D50: 5 μm), a first silicon-based active material, 0.1 wt% of SWCNT conductive material, and 3.5 wt% of CMC / SBR (binder, 1.5 / 2.0 by weight) were added to water to prepare a first negative electrode slurry.

[0075] A second negative electrode slurry was prepared in the same manner as the first negative electrode slurry, except that a second graphite-based active material in which artificial graphite and natural graphite were mixed at a weight ratio of 9:1 was used instead of the first graphite-based active material.

[0076] 96.4 wt% of granular surface-coated artificial graphite having an average particle diameter (D50) of 20 μm, 0.1 wt% of SWCNT conductive material, and 3.5 wt% of CMC / SBR (binder, 1.5 / 2.0 by weight) were added to water to prepare a third negative electrode slurry.

[0077] The prepared first negative electrode slurry, second negative electrode slurry, and third negative electrode slurry were coated on one surface of a copper current collector (copper foil having a thickness of 8 μm) and dried to form a first negative electrode active material layer, a second negative electrode active material layer, and a third negative electrode active material layer. Here, the loadings of the first negative electrode active material layer, the second negative electrode active material layer, and the third negative electrode active material layer were 5.5 mg / cm 2 , 5.5 mg / cm 2 and 2.1 mg / cm 2 . They were rolled (rolling density: 1.68 g / cm 3 ) to fabricate a negative electrode.

[0078] <Fabrication of Positive Electrode>

[0079] A slurry was prepared by mixing Li[Ni as a positive electrode active material 0.88 Co 0.1 Mn 0.02 O2, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder with each other at a weight ratio of 96.5:2:1.5. The slurry was uniformly coated on an aluminum foil having a thickness of 12 μm and dried in vacuum to fabricate a positive electrode for a secondary battery.

[0080] <Fabrication of Half Cell>

[0081] Using the prepared negative electrode and lithium metal as the counter electrode, a PE separator was placed between the negative and counter electrodes, and then an electrolyte was injected to assemble a coin cell (CR2032). The assembled coin cells were placed at room temperature for 3–24 hours to prepare a half-cell. Here, the electrolyte was prepared by mixing 1.0 M LiPF6 as a lithium salt (by volume EC:EMC = 3:7) in an organic solvent, and then mixing it with 3% by volume FEC as an electrolyte additive.

[0082] Manufacturing of Secondary Batteries

[0083] Both the positive and negative electrodes are cut (notched) to predetermined dimensions and stacked, with a separator (made of polyethylene and 13 μm thick) inserted between them to form an electrode unit. Then, each tab portion of the positive and negative electrodes is welded. The welded positive / separator / negative electrode assembly is inserted into a flexible package and sealed on three sides except for the side where the electrolyte is injected. Here, the portion with the electrode tabs is included in the sealed portion.

[0084] Inject the electrolyte into the remaining side except for the sealed part, seal the remaining side, and then soak for more than 12 hours.

[0085] An electrolyte was prepared by dissolving 1M LiPF6 in a mixed solvent of EC / EMC / DEC (volume ratio 25 / 45 / 30) and adding 1% by weight of vinylene carbonate (VC), 0.5% by weight of 1,3-propenyl sulfonyl lactone (PRS), and 0.5% by weight of lithium bis(oxalate)borate (LiBOB).

[0086] Then, pre-charge for 36 minutes at a current corresponding to 0.25C. After 1 hour, degas the battery and age it for at least 24 hours, then perform formation-charged / discharged charging (charging conditions: CC-CV 0.2C 4.2V 0.05C cutoff, discharging conditions: CC 0.2C 2.5V cutoff).

[0087] Then, perform standard charging and discharging (charging conditions: CC-CV 0.5C 4.2V 0.05C cutoff, discharging conditions: CC 0.5C 2.5V cutoff).

[0088] [Evaluation Example 1] Based on the first graphite-based active material and the second graphite-based active material (artificial graphite: natural stone) Evaluation of the formation and adhesive properties of the multilayer negative electrode active material layer (by weight) of ink.

[0089] (Examples 2 and 3, and Comparative Examples 1-3)

[0090] The negative electrode and button cell were manufactured in the same manner as in Example 1, except that the weights of artificial graphite and natural graphite in the first graphite-based active material (first layer) and the second graphite-based active material (second layer) are as shown in Table 1 below.

[0091] (Comparative Example 4)

[0092] The negative electrode and coin cell were manufactured in the same manner as in Example 1, except that the first negative electrode active material layer was prepared at 13.1 mg / cm³. 2 The loading capacity and 1.68 g / cm³ 3 The rolling density is formed on the current collector. The weight ratio of artificial graphite to natural graphite in the first graphite-based active material is shown in Table 1 below. No second negative electrode active material layer and third negative electrode active material layer are formed.

[0093] (Evaluation Method)

[0094] *Evaluation of the interfacial adhesion between the negative electrode active material layer and the current collector

[0095] The negative electrodes manufactured in Examples 1-3 and Comparative Examples 1-4 were cut into pieces with a width of 18 mm and a length of 150 mm. A 18 mm wide strip of adhesive tape was applied to the foil layer of the negative electrode, and a roller with a load of 2 kg was used to ensure sufficient adhesion. Double-sided adhesive tape was used to attach the active material layer of the negative electrode to one side of a tensile testing machine. The tape attached to the foil was then fixed to the other side of the tensile testing machine, and the adhesion force was measured. The measurement results are summarized in Table 1 below.

[0096] [Table 1]

[0097]

[0098] As can be confirmed from Table 1, compared with the comparative examples, the button batteries manufactured according to Examples 1-3 of the present invention include a first graphite-based active material (first layer) with a high natural graphite content, and exhibit excellent interfacial adhesion between the negative electrode active material layer and the current collector.

[0099] [Evaluation Example 2] Evaluation of charging characteristics and fast charging life characteristics at different rates

[0100] (Evaluation Method)

[0101] *Evaluation of charging characteristics at various rates:

[0102] After manufacturing pouch-type secondary batteries (cells) with a capacity of 20 Ah or more using the negative electrode manufactured according to the embodiments and comparative examples and the same positive electrode, the pouch-type secondary batteries (cells) were charged at a constant current rate of 0.2C until the voltage reached 4.2V, and then charging was stopped at a current rate of 0.05C while maintaining 4.2V in a constant voltage mode, thereby charging the pouch-type secondary batteries (cells) at a constant voltage. Subsequently, the pouch-type secondary batteries (cells) were discharged to 2.5V at 0.2C, and then charged at constant current rates of various rates until the voltage reached 4.2V, and then charging was stopped at a current rate of 0.05C while maintaining 4.2V in a constant voltage mode for charging evaluation. The charging characteristics at each rate were evaluated using individual cells in a chamber maintained at a constant temperature (25°C) at 0.33C / 0.5C / 1.0C / 1.5C / 1.7C / 2.0C. The charging capacity (%) in the constant current section at each charging rate was measured relative to the initial 0.2C constant current charging capacity, and the measurement results are shown in Table 2 below.

[0103] *Evaluation of Fast Charging Lifespan Characteristics

[0104] After manufacturing pouch-type secondary batteries (cells) with a capacity of 20 Ah or more using the negative electrode manufactured according to the examples and comparative examples and the same positive electrode, fast charging evaluation was conducted in a chamber set to maintain a constant temperature within the DOD 72 (SOC 8-80) range, under step-charge conditions of 1.25C / 1.0C / 0.75C / 0.5CC and discharge conditions of 1 / 3C. After repeating 100 / 200 / 300 cycles (with a 10-minute pause between charge and discharge cycles), the fast charging capacity retention rate was measured, and the measurement results are shown in Table 2 below.

[0105] [Table 2]

[0106]

[0107] As can be confirmed from Table 2, the pouch-type secondary batteries manufactured according to Examples 1-3 of the present invention include a second graphite-based active material (second layer) with a high content of artificial graphite, and therefore exhibit excellent charging capacity characteristics in the 1.5-2.0C rate range compared with the pouch-type secondary batteries manufactured according to the comparative example.

[0108] It can be confirmed that in Example 1, the total weight ratio of artificial graphite to natural graphite in the first graphite-based active material (first layer) and the second graphite-based active material (second layer) is the same as that in Comparative Example 4. However, the content of artificial graphite in the second graphite-based active material (second layer) is high, thus increasing the high-rate charging capacity due to the reduction in resistance, thereby ensuring excellent charging and output characteristics.

[0109] [Table 3]

[0110]

[0111] As can be seen from Table 3, compared with the lithium secondary batteries manufactured according to the comparative examples, the capacity retention rate (%) of the lithium secondary batteries manufactured according to Examples 1-3 decreased less over time, thereby ensuring excellent charging, lifespan, and output characteristics.

[0112] It can be confirmed that in Comparative Example 1, since the first layer structure and the second layer structure of the present invention are manufactured in opposite order, the capacity retention rate (%) after 200 cycles and 300 cycles is significantly lower than that of Example 1, thereby demonstrating the expected effect of the present invention.

[0113] Meanwhile, it can be confirmed that, compared with Examples 2 and 3, which do not fall within the preferred scope of the present invention, in Example 1, the total content of the first graphite-based active material (first layer) and the second graphite-based active material (second layer) corresponds to the preferred scope of the present invention (excessive artificial graphite), and the lifespan characteristics after 300 cycles are further improved.

[0114] [Evaluation Example 3] Evaluating battery characteristics based on the thickness variation of the negative electrode active material layer

[0115] (Examples 4-7)

[0116] The negative electrode and the button cell were manufactured in the same manner as in Example 1, except that the thicknesses of the first negative electrode active material layer and the second negative electrode active material layer were prepared as shown in Table 4 below.

[0117] (Evaluation Method)

[0118] *Evaluation of the interfacial adhesion between the negative electrode active material layer and the current collector

[0119] The negative electrodes manufactured in Examples 1 and 4-7 were evaluated in the same manner as the evaluation of the interfacial adhesion in Example 1, and the evaluation results are summarized in Table 4 below.

[0120] *Evaluation of electrode volume expansion rate during negative electrode charging

[0121] The negative electrode and coin cell manufactured in Examples 1 and 4-7 were charged at a constant current at a rate of 0.1C at room temperature (25°C) until the voltage reached 0.01V (relative to Li). Charging was then stopped at a current rate of 0.01C while maintaining a constant voltage of 0.01V, thus charging the negative electrode and coin cell at a constant voltage. Discharging was performed at a constant current rate of 0.1C until the voltage reached 1.5V (relative to Li). One charge-discharge cycle was defined as one cycle, and another charge-discharge cycle was performed in the same manner before disassembling the coin cell.

[0122] The thickness of the uncharged negative electrode (SOC0) and the thickness of the charged negative electrode (SOC100) were measured, and the comparison results are summarized in Table 4 below.

[0123] *Evaluation of electrode stripping during negative electrode charging

[0124] The negative electrode and coin cell manufactured in Examples 1 and 4-7 were charged at a constant current at a rate of 0.1C at room temperature (25°C) until the voltage reached 0.01V (relative to Li). Charging was then stopped at a current rate of 0.01C while maintaining a constant voltage of 0.01V, thus charging the negative electrode and coin cell at a constant voltage. Discharging was performed at a constant current rate of 0.1C until the voltage reached 1.5V (relative to Li). One charge-discharge cycle was defined as one cycle, and another charge-discharge cycle was performed in the same manner before disassembling the coin cell.

[0125] The charged negative electrode was left to stand at room temperature (25°C) for 10 minutes without separate cleaning. The state of the adhesion between the substrate surface and the active material layer was visually confirmed. The results are summarized in Table 4 below.

[0126] [Table 4]

[0127]

[0128]

[0129] (In Table 4, "NG:AG" represents the total weight ratio of natural graphite to synthetic graphite in the first and second layers.)

[0130] Referring to Table 4, in Example 1, where the first and second layers are formed with the preferred thickness ratio of the present invention, the volume expansion rate of the charging electrode is low, and no peeling occurs in the fully charged electrode. On the other hand, in Examples 4 and 5, peeling occurs in the fully charged electrode, while in Examples 6 and 7, the electrode adhesion is excellent and no electrode peeling occurs, but the volume expansion rate of the charging electrode is too high, thereby reducing the energy density, which is undesirable.

[0131] [Evaluation Example 4] Evaluation of battery characteristics based on variations in the composition and thickness of the third negative electrode active material layer

[0132] (Examples 8-13)

[0133] The negative electrode, button cell, and secondary cell were manufactured in the same manner as in Example 1, except that the type of the third graphite-based active material (artificial or natural graphite) in the third negative electrode active layer and the thickness of the third negative electrode active layer are shown in Table 5 below.

[0134] (Evaluation Method)

[0135] *Evaluation of electrode volume expansion rate during negative electrode charging

[0136] The negative electrodes manufactured in Examples 1 and 8-13 were evaluated in the same manner as the volume expansion rate evaluation of the charging electrode in Example 3. The evaluation results are summarized in Table 5 below.

[0137] *Evaluation of battery energy density

[0138] After manufacturing pouch-type secondary batteries (cells) with a capacity of 20 Ah or more using the negative electrode and the same positive electrode manufactured in Examples 1 and 8-13, the pouch-type secondary batteries (cells) were charged at a constant current rate of 0.3C until the voltage reached 4.2V. Charging was then stopped at a current rate of 0.05C while maintaining a constant voltage of 4.2V, thus charging the pouch-type secondary batteries (cells) at a constant voltage. Subsequently, they were discharged at a constant current rate of 0.3C until the voltage reached 2.5V. The discharge capacity (Ah) and energy (Wh), as well as the volume of each battery at a charging state of 4.2V, were measured to calculate the volumetric energy density. The results are summarized in Table 5 below.

[0139] *Evaluation of Fast Charging Lifespan Characteristics

[0140] The secondary batteries manufactured in Examples 1 and 8-13 were evaluated in the same manner as those evaluated in Example 2 for their fast charging life characteristics. The evaluation results are summarized in Table 5 below.

[0141] [Table 5]

[0142]

[0143] (The thickness (%) of the third negative electrode active material layer is based on the total thickness (%) of the negative electrode active material layer.)

[0144] As can be seen from Table 5, in the embodiment where a third layer is formed, the introduction of the third layer reduces electrolyte side reactions and exhibits an effect of suppressing electrode expansion, thereby enabling high energy density. Specifically, unlike the first and second layers, the third layer does not contain silicon-based active materials, thus preventing irreversible decomposition of the electrolyte caused by silicon-based materials, thereby suppressing excessive expansion of the silicon-based negative electrode active material layer due to electrode charging. Through the above effects, the chemical and mechanical safety of the negative electrode can be improved, thereby increasing the long-term lifespan of the lithium secondary battery, and increasing energy density by compensating for the expansion thickness of the negative electrode during charging.

[0145] Furthermore, it can be confirmed that, compared with Examples 1, 8, and 9 which have the preferred third layer thickness of the present invention, the examples without the preferred third layer thickness are disadvantageous in terms of energy density (Example 10) or the side reactions of the electrolyte are not sufficiently suppressed, resulting in an increase in electrode expansion rate (Example 11).

[0146] Meanwhile, it was found that when natural graphite was used as the third negative electrode active material, the slightly lower hardness of the natural graphite particles was compressed during the electrode rolling process, making it difficult for the electrolyte to penetrate into the electrode. This made it impossible to ensure the ion migration path, thereby reducing the battery's lifespan characteristics.

[0147] [Evaluation Example 5] Evaluation of battery characteristics based on the content of various silicon-based active materials

[0148] (Examples 14-17)

[0149] The negative electrode, button cell, and secondary cell were manufactured in the same manner as in Example 1, except that the contents of the first silicon-based active material and the second silicon-based active material in the first negative electrode active material layer and the second negative electrode active material layer were the same as those in Table 6 below.

[0150] (Evaluation Method)

[0151] *Evaluation of electrode volume expansion rate during negative electrode charging

[0152] The negative electrodes manufactured in Examples 1 and 14-17 were evaluated in the same manner as the volume expansion rate evaluation of the charging electrode in Example 3, and the evaluation results are summarized in Table 6 below.

[0153] *Evaluation of battery energy density

[0154] The secondary batteries manufactured in Examples 1 and 14-17 were evaluated in the same manner as the battery energy density evaluation in Example 4, and the evaluation results are summarized in Table 6 below.

[0155] *Evaluation of Fast Charging Lifespan Characteristics

[0156] The negative electrodes manufactured in Examples 1 and 14-17 were evaluated in the same manner as the volume expansion rate evaluation of the charging electrode in Example 3, and the evaluation results are summarized in Table 6 below.

[0157] *Evaluation of Fast Charging Lifespan Characteristics

[0158] The secondary batteries manufactured in Examples 1 and 14-17 were evaluated in the same manner as those evaluated in Example 2 for their fast charging life characteristics. The evaluation results are summarized in Table 6 below.

[0159] * Evaluation of (general) charging life characteristics

[0160] The general charge life characteristics of the secondary batteries manufactured in Examples 1 and 14-17 within the DOD94 (SOC2-96) range were evaluated in a chamber maintained at 35°C. The secondary batteries were charged at 0.3C to the voltage corresponding to SOC96 under constant current / constant voltage (CC / CV) conditions, and charging was stopped at 0.05C. Then, the secondary batteries were discharged at 0.3C to the voltage corresponding to SOC2 under constant current (CC) conditions, and the discharge capacity was measured. After repeating the above process 500 cycles, the discharge capacity retention rate for evaluating the (general) charge life characteristics was measured, and the measurement results are summarized in Table 6 below.

[0161] [Table 6]

[0162]

[0163] (The contents of the first silicon-based active material and the second silicon-based active material are respectively weight % based on the total weight of the active materials in the first negative electrode active material layer and the second negative electrode active material layer.)

[0164] Referring to Table 6, all secondary batteries in Examples 1 and 14-17 exhibit excellent (general) 500-cycle fast charging life characteristics. However, when the content of silicon-based active material increases to 20% by weight or more, the 100-cycle fast charging life characteristics tend to decrease to 80% or greater and less than 90%. Therefore, referring to Table 3, in the case of the secondary battery in Example 1, considering that the 300-cycle life remains at a very high level under the same fast charging life characteristic evaluation conditions, whether the battery used for fast charging maintains a capacity retention rate of over 90% after 100 fast charging cycles can be used as an indicator for commercialization.

[0165] Meanwhile, if the content of silicon-based active material is less than 6% by weight, even if the volume expansion rate of the battery is reduced, its energy density will be too low, and it is inappropriate to be below 700Wh / L.

[0166] In summary, this invention can contain a higher content of silicon-based active material than related technologies by varying the mixing ratio of natural graphite and artificial graphite in each layer of a multilayer negative electrode active material containing silicon-based material. This improves the adhesion to the negative electrode current collector and reduces the interfacial resistance, thereby achieving high energy density (above 700 Wh / L) and improving performance such as negative electrode peeling, general lifetime characteristics, and fast lifetime characteristics. Preferably, even if the total weight of the active material in the first and second layers is 6-30% by weight, more preferably 6-20% by weight, and even more preferably 9-20% by weight, the high content of silicon-based active material is preferred because it can achieve a fast charge cycle life characteristic of more than 90% for 100 cycles and a fast charge cycle life characteristic of more than 80% for 300 cycles.

[0167] By preparing a multilayer negative electrode active material layer, in which the mixing ratio of natural graphite and artificial graphite is applied differently in the electrode thickness direction, battery degradation caused by volume expansion of silicon-based materials and side reactions of electrolyte can be suppressed, and high-rate charging characteristics can be improved by reducing resistance.

[0168] The first negative electrode active material layer is a coating used to improve the adhesion between the silicon-based material and the negative electrode current collector. The adhesion can be improved by increasing the proportion of natural graphite-based material and minimizing the proportion of artificial graphite-based material in the graphite-based material.

[0169] The second negative electrode active material layer is a coating used to improve the high-rate charging characteristics of the coating containing silicon-based materials, and the high-rate charging characteristics can be improved by increasing the proportion of artificial graphite-based materials and minimizing the proportion of natural graphite-based materials in the graphite-based materials.

[0170] The active material of the third negative electrode active material layer consists only of graphite-based materials, which can reduce the resistance at the electrode interface and minimize the side reactions between the electrolyte and silicon-based materials.

[0171] While embodiments of the present invention have been described above, the invention is not limited to the above embodiments and can be made in various different forms. Those skilled in the art will understand that various modifications and alterations can be made without changing the technical concept or essential characteristics of the invention. Therefore, it should be understood that the examples described above are illustrative in all respects and not restrictive.

Claims

1. A negative electrode for a lithium secondary battery, comprising: current collector; A first negative electrode active material layer is disposed on the current collector and includes a first graphite-based active material containing artificial graphite and natural graphite and a first silicon-based active material; and A second negative electrode active material layer is disposed on the first negative electrode active material layer and includes a second graphite-based active material containing artificial graphite and natural graphite, and a second silicon-based active material. In this embodiment, the content of artificial graphite in the first graphite-based active material is equal to or less than the content of natural graphite, while the content of artificial graphite in the second graphite-based active material is greater than the content of natural graphite. The negative electrode for the lithium secondary battery further includes a third negative electrode active material layer, which is disposed on the second negative electrode active material layer and includes a third graphite-based active material containing artificial graphite. The second graphite-based active material comprises artificial graphite and natural graphite in a weight ratio of 90:10 to 60:

40. The thickness ratio between the first negative electrode active material layer and the second negative electrode active material layer is greater than 3:7 and less than 7:

3. The thickness of the third negative electrode active material layer is 0.5%-15%, based on the total thickness of the negative electrode active material layer.

2. The negative electrode for a lithium secondary battery according to claim 1, wherein the first graphite-based active material comprises artificial graphite and natural graphite in a weight ratio of 5:95 to 50:

50.

3. The negative electrode for a lithium secondary battery according to claim 1, wherein, The first negative electrode active material layer comprises 0.1-35% by weight of the first silicon-based active material based on the total weight of the active material, and The second negative electrode active material layer contains 0.1-35% by weight of the second silicon-based active material based on the total weight of the active material.

4. The negative electrode for a lithium secondary battery according to claim 3, wherein the first negative electrode active material layer comprises 6-30% by weight of the first silicon-based active material based on the total weight of the active material, and The second negative electrode active material layer contains 6-30% by weight of the second silicon-based active material based on the total weight of the active material.

5. The negative electrode for a lithium secondary battery according to claim 1, wherein the third graphite-based active material is granular or bimodal artificial graphite and has a particle size of 13-20 μm.

6. The negative electrode for a lithium secondary battery according to claim 1, wherein the density of the third negative electrode active material layer is 1.55-1.8 g / cm³. 3 .

7. The negative electrode for a lithium secondary battery according to claim 1, wherein the first negative electrode active material layer and the second negative electrode active material layer have a continuous active material concentration gradient at their interface.

8. A lithium secondary battery comprising a negative electrode, a positive electrode, a separator, and an electrolyte as described in any one of claims 1-7.

Citation Information

Patent Citations

  • Lithium ion secondary battery

    CN103733391A

  • Negative electrode for lithium secondary battery and lithium secondary battery comprising the same

    CN107785535A

  • Multi-layer anode comprising natural graphite and artificial graphite, and lithium secondary battery comprising same

    CN108701816A